FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELELAHAN KERJA PADA PERAWAT DI RSUD INDRAMAYU - Widyastuti, Setyo; Rudiansyah; Nuhilwa Nabilah, Betris (JURNAL SMART ANKes, 2025)
Background: Nurses are one of the professions with a high risk of work accidents, the main factor underlying work accidents is fatigue. Fatigue conditions can reduce concentration and alertness, this makes it easier for nurses to make mistakes and not pay attention to potential hazards in the work environment. Work fatigue can occur influenced by 2 factors, namely internal and external factors, internal factors include nutritional status, health conditions, and length of service. While external factors include workload, work shifts, work stress and work environment. Objective: This study aims to determine the factors associated with work fatigue in nurses. Method: The method used in this study was an analytic survey with a cross sectional approach. The study population was all 315 inpatient nurses with a sample of 101 people taken using accidental sampling technique. Data analysis using univariate and bivariate analysis using Pearson Chi-Square test statistics. Results: The results showed that there was no relationship between health conditions, nutritional status, and length of service with job fatigue. However, there was a significant relationship between mental workload (P=0.000) and occupational stress (P=0.002) with job fatigue. Conclussion: This study concludes that factors related to work fatigue in nurses are mental workload and work stress.. Therefore, it is necessary to increase the number of nurses as needed as well as improve the quality of the work environment and stress management